Penggunaan Jahe Merah untuk Menurunkan Intensitas Nyeri Haid pada Remaja - Siswi Wulandari (VISIKES: Jurnal Kesehatan Masyarakat, 2018)
Menstrual pain is a symptoms and was not a diseases caused by hiperkontraktilitas the uterus caused by prostaglandins. Research purposes is identified influence of red ginger water towards the intensity of menstrual pain. Research purposes is identified influence of red ginger water towards the intensity of menstrual pain on students D3 midwifery second semester. This research uses quasi-experiment method. The population is that suffer from menstrual pain as many as 26 people. The sampling method is total population. The analysis is bivariate analysis using wilcoxon test. Based on the results of the statistics got that on respondents the intervention group were given before treatment (61,5%) or 8 people suffer from mild pain, after given treatment (46,2%) or 6 people did not experience pain, respondents group controls on first observation (69,2%) or 9 people suffer from mild pain, on second observation (69,2%) or 9 people suffer from mild pain. The result of the statistic test using wilcoxon test in the intervention group shows the p-value = 0,001 with CI of 95% (Î± = 0,005) it can be said that p-value <Î±so that Ho is rejected and H1 is accepted.